1987
DOI: 10.1017/s0950268800068059
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic relationship of West Nile strains by titre ratios calculated from cross-neutralization test results

Abstract: SUMMARYThe antigenic relationship of ten South African West Nile isolates, the South African prototype virus H442, the Egyptian strain EGlO1 and the Indian strain G2266 were compared using titre ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…We observed variation in neutralization sensitivity that did not define the difference between lineage I and II viruses. Variation in neutralization sensitivity is consistent with previous observations for WNV and Yellow fever virus (Hammam et al, 1965;Peiris et al, 1982;Blackburn et al, 1987). In PRNT 90 tests, WN-DAK (22?7 %) was significantly more sensitive to neutralization by bird sera than either WN-NY (2?6 %) or WN-Is (5?0 %).…”
Section: Discussionsupporting
confidence: 90%
“…We observed variation in neutralization sensitivity that did not define the difference between lineage I and II viruses. Variation in neutralization sensitivity is consistent with previous observations for WNV and Yellow fever virus (Hammam et al, 1965;Peiris et al, 1982;Blackburn et al, 1987). In PRNT 90 tests, WN-DAK (22?7 %) was significantly more sensitive to neutralization by bird sera than either WN-NY (2?6 %) or WN-Is (5?0 %).…”
Section: Discussionsupporting
confidence: 90%
“…Strain differences between St. Louis encephalitis viruses isolated from various geographical areas have also been detected [32]. On the basis of the MAb reactivities with the WN isolates from the Rondebult bird sanctuary four distinct strains can be recognized, supporting the findings of Blackburn et al [1]. While some isolates appeared to be the same strain as the H442 virus, others lacked the H442 strainspecific determinant defined by one of the MAbs (2D 12).…”
Section: Discussionsupporting
confidence: 70%
“…Strains from Africa, Europe, the U.S.S.R. and Middle East formed the Palearctic antigenic group serologically distinct from strains isolated in India [10,15]. Antigenic variation has, however, been shown to occur between West Nile (WN) strains isolated within a single region [1,27,28,39].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that previous infection with heterologous flaviviruses reduces the incidence of encephalitis and can provide protection from fatal WNV challenge in a hamster model for WNV pathogenesis ( 20 , 21 ). In contrast, a neutralization study performed with WNV strains of different lineages demonstrated that neutralizing antibodies against an Indian WNV strain provided poor protection against a South African WNV strain ( 22 ). Our results demonstrated that prior immunization with KUN virus can provide protection from lethal NY99 challenge in crows.…”
Section: Discussionmentioning
confidence: 99%